Women in love [videorecording (DVD)] - Russell, Ken, 1927-2011; Jackson, Glenda; Linden, Jennie, 1939-; Bates, Alan, 1934-2003; Lawrence, D. H. (David Herbert), 1885-1930 (Criterion collection, 2018)
Two sisters fall in love with two best friends and have markedly different experiences in their relationships.